Teachers’ Trends in Teaching Arabic in Elementary Schools - Abdul Haris; MD. Qutbuddin; Ahmad Fatoni (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
This study aims to describe the teachers’ trends in teaching Arabic in elementary schools in terms of goal orientations and teaching techniques. The research data was collected from 52 Arabic teachers using a questionnaire and interviews. The data was analyzed using the interactive techniques of Miles and Huberman. The results of the study show that in relation to the goal orientation, the teachers give priority to the mastering of vocabulary (34.6 %), followed by speaking (25 %), reading (23.1 %), and the last is writing, listening, and translating (1.9 %). This fact indicated that their goal orientations have not led to the expected goals as stated in the curriculum. This study also shows that their techniques in teaching Arabic have various patterns based on their main goal orientations that did not follow the standard of teaching techniques as suggested by the Arabic education experts. The results of this study indicate that teachers’ lack of competence in teaching Arabic in elementary schools.